2018
DOI: 10.1016/j.jdiacomp.2018.01.002
|View full text |Cite
|
Sign up to set email alerts
|

Sex-specific differences in insulin resistance in type 1 diabetes: The CACTI cohort

Abstract: We found that type 1 diabetes affected adipose and skeletal muscle insulin sensitivity to a greater extent in women than in men, perhaps contributing to the greater relative increase in cardiovascular risk in women with type 1 diabetes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 33 publications
2
18
0
Order By: Relevance
“…Another important finding of our study is that the association between the TyG index and the risk of MI was more pronounced in women than men, which is in accordance with previous studies [ 34 , 35 ]. A cohort study showed that higher fasting serum insulin levels and HOMA-IR were associated with incident hypertension in women, but not in men [ 34 ].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Another important finding of our study is that the association between the TyG index and the risk of MI was more pronounced in women than men, which is in accordance with previous studies [ 34 , 35 ]. A cohort study showed that higher fasting serum insulin levels and HOMA-IR were associated with incident hypertension in women, but not in men [ 34 ].…”
Section: Discussionsupporting
confidence: 93%
“…A cohort study showed that higher fasting serum insulin levels and HOMA-IR were associated with incident hypertension in women, but not in men [ 34 ]. Moreover, the Coronary Artery Calcification in Type 1 Diabetes cohort study found that type 1 diabetes affected adipose and skeletal muscle insulin sensitivity to a greater extent in women than in men, which might have contributed to the greater relative increase in cardiovascular risk in women [ 35 ]. A possible mechanism for this finding may be a role of estrogen in premenopausal cardiovascular protection and enhanced insulin sensitivity.…”
Section: Discussionmentioning
confidence: 99%
“…[20,22] Our findings might be, to a certain extent, explained by the high magnitude of insulin resistance and the direct impact of insulin resistance and hormonal status on enzymes implicated in lipid/lipoprotein metabolism in females. [16,23] However, the males predominated among those with combined high plasma Tg/low plasma HDL-C and mixed high plasma Tg/high plasma LDL-C/low plasma HDL-C lipid/lipoprotein abnormalities. This finding has potential clinical consequence, given the well-known relationship between combined and mixed lipid/lipoprotein abnormalities and their various adverse vascular events in DM [2][3][4][5][6].…”
Section: Discussionmentioning
confidence: 99%
“…The development of IR is also related to the gender of T1DM patients. Millstein et al found that T1DM affected adipose and skeletal muscle insulin sensitivity to a greater extent in women than in men [ 25 ]. Participants in the control groups presented higher Morbus values (M-values) than those with DM, regardless of gender.…”
Section: What Does It Mean To Be Insulin Resistant?mentioning
confidence: 99%